Low-field MRI at high magnetic field instability and inhomogeneity conditions - Rodriguez, Gonzalo G.; Schürrer, Clemar A.; Anoardo, Esteban (Frontiers in Physics, 2023)
Understanding the effects of the magnetic field time instabilities in magnetic resonance imaging (MRI) is fundamental for the success of portable and low-cost MRI hardware based on electromagnets. In this work we propose a magnetic field model that considers the field instability in addition to the inhomogeneity. We have successfully validated the model on signals acquired with a commercial NMR instrument. It was used to simulate the image defects due to different types of instability for both the spin-echo and the gradient-echo sequences. We have considered both random field fluctuations, and an instability having a dominant harmonic component. Strategies are suggested to minimize the artifacts generated by these instabilities. Images were acquired using a home-made MRI relaxometer to show the consistency of the analysis.